Web-based information system of psychological test employee acceptance - Irawan Y.F.; Nguyen P.T.; Rema Devi S.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
In every institution, it is definitely needed employees workers who manage the company so that it can run the activities of companies that use HR (Human Resources) one of them is in the education field, it needs workers who manage it, so that it can run teaching and learning activities well. In the procurement of labor or employees that must be really selective, to maximize performance in their respective duties. The development of technology is very possible that the information system is not only used as a tool for the implementation of the lecture process but it can also be used in the implementation of the web-based recruitment test. A web-based information system will be designed and developed to enable the employee selection process in a psychological test to be more selective and easier. BEIESP.